Schistosomiasis Interventions in Africa: Assessment and Systematic Review - Christopher Yaw Dumevi; George Boateng Kyei; Patience B. Tetteh-Quarcoo; James-Paul Kretchy; Irene Ayi; Patrick F. Ayeh-Kumi (Journal of Parasitology Research)
Conclusion: There is a paucity of data on a systematic approach by the national governments of Africa that effectively integrates pharmacological and nonpharmacological control strategies to meet the 2030 elimination roadmap targets.